2015
DOI: 10.1021/acs.jpca.5b03404
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of Sm3+ in Nanocrystalline BaFCl

Abstract: We demonstrate that exposure of nanocrystalline BaFCl:Sm(3+) X-ray storage phosphor to blue laser pulses with peak power densities on the order of 10 GW/cm(2) results in conversion of Sm(3+) to Sm(2+). This photoreduction is found to be strongly power-dependent with an initial fast rate, followed by a slower rate. The photoreduction appears to be orders of magnitude more efficient than that for previously reported systems, and it is estimated that up to 50% of the samarium ions can be photoreduced to the dival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Materials doped with Sm 2+ have gained a growing interest over the past decades in various applications, starting back to the conception of lasers in the 1960s. They take advantage of specificities of the Sm 2+ electronic structure over other compounds. Its 5 D 0 – 7 F 0 transition is thereby nondegenerate, and in cases where it is observable (especially in C n and C nv compounds where it is symmetry-allowed), the number of lines experimentally detected directly indicates the number of crystallographic sites actually occupied by the ions. , The Sm 2+ luminescence being also pressure- and temperature-dependent, some doped crystals are used as sensors in a more extended and precise way than the historically used ruby. Sm 2+ -activated matlockites have also been the subject of numerous studies about their photon-gated spectral hole-burning properties for optical data storage. More recently, BaFCl:Sm 2+ has proved to be a stable and reliable X-ray and UV storage phosphor. Its mechanism is based on the photoreduction of Sm 3+ upon X-ray or UV exposure and the subsequent strong 5 D J – 7 F J luminescence arising from the divalent ion . With the view of extending the range of applications for Sm 2+ -doped materials in the future, it appears necessary to gain more insight into its electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…Materials doped with Sm 2+ have gained a growing interest over the past decades in various applications, starting back to the conception of lasers in the 1960s. They take advantage of specificities of the Sm 2+ electronic structure over other compounds. Its 5 D 0 – 7 F 0 transition is thereby nondegenerate, and in cases where it is observable (especially in C n and C nv compounds where it is symmetry-allowed), the number of lines experimentally detected directly indicates the number of crystallographic sites actually occupied by the ions. , The Sm 2+ luminescence being also pressure- and temperature-dependent, some doped crystals are used as sensors in a more extended and precise way than the historically used ruby. Sm 2+ -activated matlockites have also been the subject of numerous studies about their photon-gated spectral hole-burning properties for optical data storage. More recently, BaFCl:Sm 2+ has proved to be a stable and reliable X-ray and UV storage phosphor. Its mechanism is based on the photoreduction of Sm 3+ upon X-ray or UV exposure and the subsequent strong 5 D J – 7 F J luminescence arising from the divalent ion . With the view of extending the range of applications for Sm 2+ -doped materials in the future, it appears necessary to gain more insight into its electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced luminescence of Eu 3+ in the presence of Tb 3+ is explicable as per the Dieke diagram based on energy transfer from the latter to the former as illustrated in Figure . , However, in stark contrast, fundamental understanding of activation channels, recombination pathways, and sensitization mechanisms upon high-energy excitation has not thus far been elucidated in this system. VUV and soft X-ray excitation near the elemental edges of the host lattice gives rise to high-energy electron–hole pairs that can thermalize to activate luminescent centers, which then decay through a variety of radiative and nonradiative recombination pathways. , Interestingly, while some authors have demonstrated Sm 3+ to Sm 2+ reduction in similar matlockite structures upon deep UV exposure, prolonged exposure of the LaOCl nanocrystals presented here to soft X-rays results in beam damage and nonspecific diminution of XEOL intensity without any discernible photoinduced reduction of Eu 3+ sites (which would be observed as an increase in intensity of Eu 2+ bands). , As noted above, exposure at a particular spot is limited to 10 ms in order to avoid beam damage from high-intensity synchrotron radiation.…”
Section: Resultsmentioning
confidence: 80%
“…23,46−48 Interestingly, while some authors have demonstrated Sm 3+ to Sm 2+ reduction in similar matlockite structures upon deep UV exposure, prolonged exposure of the LaOCl nanocrystals presented here to soft X-rays results in beam damage and nonspecific diminution of XEOL intensity without any discernible photoinduced reduction of Eu 3+ sites (which would be observed as an increase in intensity of Eu 2+ bands). 49,50 As noted above, exposure at a particular spot is limited to 10 ms in order to avoid beam damage from highintensity synchrotron radiation. Figure 6 shows La N 4,5 -edge (4d → 4f) XANES spectra acquired in FLY mode for solid-solution La 0.889 Eu 0.111 OCl, La 1−x−y Tb x Eu y OCl, and La 0.911 Tb 0.089 OCl phosphors in the range between 95−150 eV.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Rare-earth ion-doped alkaline-earth fluorohalides with the PbFCl (matlockite) structure (e.g., BaFCl and BaFBr) exhibit high storage efficiencies when subjected to X-irradiation and are widely used in computed radiography, especially for intraoral dental imaging . They also have considerable potential for applications in dosimetry and optical data storage. Recently, BaLiF 3 has emerged as a promising alternative host material for storage phosphors, in addition to its applications as an ion conductor, a scintillator, , and a tunable ultraviolet laser. , The storage mechanism in alkaline-earth fluorohalides doped with rare-earth ions is reasonably well-understood. ,, In contrast, fluoroperovskites (ABF 3 ) are less well-understood, and they remain the subject of an active area of research with some attention focused on BaLiF 3 . As such, for a better understanding and to realize potential practical implementations, the investigation of BaLiF 3 activated with a broad range of rare-earth elements is required.…”
Section: Introductionmentioning
confidence: 99%